Plasma Purification Treatment Relieves the Damage of Hyperlipidemia to PBMCs - Zhang, Xiao Meng; Gu, Yan Hong; Deng, Hao; Xu, Zheng Quan; Zhong, Ze Yuan; Lyu, Xia Jie; Jin, Hui Min; Yang, Xiu Hong (Frontiers in Cardiovascular Medicine, 2021)
Background Hyperlipidaemia [hypercholesterolemia (cholesterol>5.18 mmol/L) or hypertriglyceridemia (triglycerides>2.3 mmol/L), mixed hyperlipidaemia (cholesterol>5.18 mmol/L and triglycerides>2.3 mmol/L), and high low-density lipoproteinemia (low-density lipoprotein>3.4 mmol/L)] is a strong risk factor for arteriosclerosis and cardiovascular disease (CVD). Therapy with lipid-lowering drugs often results in many side effects. Our study aimed to investigate the potential effects of non-drug therapy with double-filtration plasmapheresis (DFPP) on lipid metabolism-, endoplasmic reticulum (ER) stress- and apoptosis-related proteins in peripheral blood mononuclear cells (PBMCs) before and after lipid clearance in patients with hyperlipidaemia. Methods Thirty-five hyperlipidaemia patients were selected. Proteins related to lipid metabolism [CD36, proprotein convertase subtilisin/kexin type 9 (PCSK9) and LDL receptor], ER stress [glucose-regulated protein 78 (Grp78), C/EBP homoiogousprotein (CHOP), Activating Transcription Factor 4 (ATF4), eukaryotic initiation factor2α (EIF2α)], and apoptosis [B-cell lymphoma-2 (Bcl-2), BAX, and cysteinyl aspartate specific proteinase-3 (Caspase-3)]were assayed by western blot, reactive oxygen species (ROS) were measured by flow cytometry (FCM), and ELISA detected serum inflammatory (IL-1 IL-6, TNF-α) factors. Results Compared with their pre-DFPP values, the values of most lipid metabolic parameters, such as cholesterol, triglycerides, LDL, lipoprotein a [Lp(a)] and small dense LDL cholesterol (sdLDL), were reduced after DFPP. DFPP was associated with the downregulation of proteins related to lipid metabolism, ER stress and apoptosis, resulting in decreased ROS and serum inflammatory factor release. Conclusion DFPP has lipid-lowering activity and can also regulate lipid metabolism-, ER stress- and apoptosis-related proteins in PBMCs and reduce the levels of inflammatory factors in patients with hyperlipidaemia (ClinicalTrials.gov number: NCT03491956).